THE CHALLENGE OF PEER FEEDBACK IN EFL WRITING CLASSROOM: - Ummi Salamah Tianotak (EDU Journal - English Department of UMMU Journal, 2021)
Peer feedback has recently become the most popular technique in teaching writing since a large number of research have been conducted to investigate its advantages of it. In contrast, there are numerous studies investigating the drawbacks of peer feedback in EFL students. As a debatable concept, peer feedback will always be controversial since various findings are found by the researchers. Therefore, this paper firstly introduces peer feedback, then, attempts to elaborate the challenges of peer feedback viewed from EFL students’ perspectives in learning writing, and finally proposes some recommendations of the effective implementation of peer feedback. To overcome the challenges, there are some things that must be considered such as conducting training for students before the implementation, creating a comfortable environment, and grading the peer reviewer draft.